Optimisation of at-sea culture and harvest conditions for cultivated Macrocystis pyrifera: yield, biofouling and biochemical composition of cultured biomass - Biancacci, C.; Visch, W.; Callahan, D. L.; Farrington, G.; Francis, D. S.; Lamb, P.; McVilly, A.; Nardelli, A.; Sanderson, J. C.; Schwoerbel, J.; Hurd, C. L.; Evans, B.; et al. (Frontiers in Marine Science, 2022)
Seaweed cultivation is gaining interest world-wide for both food and non-food applications. Global seaweed aquaculture production currently exceeds 32 Mt wwt per annum but is dominated (86% of total) by Asian countries. To meet future demand for seaweed products, regions beyond Asia with aquaculture production potential are being explored. The goal of this study was to assess the suitability of the native kelp Macrocystis pyrifera, for aquaculture in Tasmania, south-eastern Australia. M. pyrifera was cultivated on seeded twine on loops (1 – 5 m depth) along 100-m longlines at two sites (Oakhampton Bay and Great Taylor Bay) from April to November 2020. Temporal and spatial variability in (1) yield (kg wwt m-1), (2) biofouling (% coverage), and (3) biochemical composition (including proximate composition, fatty acids, dietary minerals, heavy metal profiling, C, N, H, S concentrations and C:N ratio, antioxidants (phenolic compounds), and pigments (Chl-a, Chl-c, fucoxanthin)) were compared amongst the two cultivation sites, at two depths (1 and 5 m) from harvests between July – November 2020. Yield (kg m-1, wwt) did not significantly change across harvest times, but was greater at a depth of 1 m compared to 5 m. Biofouling on the kelp blades increased significantly in early spring (September). The biochemical composition of the cultured biomass varied over time, between sites and with depth for most of the compounds analysed. Higher lipid, protein and ash content was reported at Okehampton Bay compared to Great Taylor Bay cultures and at 5 m compared to 1 m depth, and levels of these macronutrients decreased during the harvest period. The combined results of yield, biofouling, and biochemical composition suggest that, for an April deployment at the sites investigated, M. pyrifera should be harvested in July-August (mid to late winter) to optimise yield and quality of the cultured kelp biomass. These findings provide a better understanding of the variation in growth and quality of cultivated M. pyrifera biomass in the region, and inform future management and development of kelp aquaculture in south-eastern Australia and in a global context.